Establishing a model for family mediation in Malaysia: replacing the marriage tribunal under the national registration department - Abdul Hak, Nora; Ibrahim, Norliah; Rahmat, Nur Ezan (2014)
Dispute resolution outside of court is not new; societies world-over have long used non-judicial and indigenous methods to resolve conflicts. Family disputes, more often than not, are rarely concerned with matters of fact but is almost invariably complicated by the intense and intimate emotions of the parties in conflict. Therefore, the utilization of other processes, such as conciliation and mediation, independent of litigation will lead to a more satisfactory resolution of disputes rather than relying on the judgments of the court of law. Section 55(2) of the Law Reform (Marriage and Divorce) Act 1976 provides that even when the parties have presented a petition for divorce, if it appears to the court at any stage of the proceedings that there is a reasonable possibility of a reconciliation between them, the court may adjourn the proceedings for such period as it thinks fit to enable attempts to be made to affect such a reconciliation. In the case of a petition for divorce based on the irretrievable breakdown of the marriage, the petitioner must first refer the matrimonial difficulty to a conciliatory body before filing the petition. No person shall petition for divorce, except under sections 51 and 52 of the 1976 Act, unless he or she has first referred the matrimonial difficulty to a conciliatory body and that body has certified that it has failed to reconcile the parties. Practitioners of family law are of the view that the conciliation process in Malaysia has not been very successful in helping disputing couples resolving their problems and this is supported by statistics which shows that the success rate for these reconciliation sessions is very low. This research highlights on some emerging issues related to the effectiveness of conciliatory bodies appointed under section 106 of the 1976 Act especially the Marriage Tribunal under the National Registration Department (NRD). It highlights the problems and constraints faced by the conciliatory bodies and will suggest amendments to the law and policy.